Genotyping-by-Sequencing-Based Genetic Analysis of African Rice Cultivars and Association Mapping of Blast Resistance Genes Against Magnaporthe oryzae Populations in Africa - Mgonja, Emmanuel M.; Park, Chan Ho; Houxiang Kang; Balimponya, Elias G.; Opiyo, Stephen; Bellizzi, Maria; Mutiga, Samuel Kilonzo; Rotich, Felix; Ganeshan, Veena Devi; Mabagala, Robert; Sneller, Clay H.; Correll, James C.; et al. (Scientific Societies, 2017)
Understanding the genetic diversity of rice germplasm is important for the sustainable use of genetic materials in rice breeding and production. Africa is rich in rice genetic resources that can be utilized to boost rice productivity on the continent. A major constraint to rice production in Africa is rice blast, caused by the hemibiotrophic fungal pathogen Magnaporthe oryzae. In this report, we present the results of a genotyping-by-sequencing (GBS)-based diversity analysis of 190 African rice cultivars and an association mapping of blast resistance (R) genes and quantitative trait loci (QTLs). The 190 African cultivars were clustered into three groups based on the 184K single nucleotide polymorphisms generated by GBS. We inoculated the rice cultivars with six African M. oryzae isolates. Association mapping identified 25 genomic regions associated with blast resistance (RABRs) in the rice genome. Moreover, PCR analysis indicated that RABR_23 is associated with the Pi-ta gene on chromosome 12. Our study demonstrates that the combination of GBS-based genetic diversity population analysis and association mapping is effective in identifying rice blast R genes/QTLs that contribute to resistance against African populations of M. oryzae. The identified markers linked to the RABRs and 14 highly resistant cultivars in this study will be useful for rice breeding in Africa.